Analisis Stakeholder Engagement Blibli Tiket Action dalam Event Langkah Membumi Festival 2024 - Angkawibawa, Harla Nathalya; Elkezia, Natasha; Akbari, Taufan Teguh (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Business success is not only measured by its financial profits, but also by its environmental and social impact. The concepts of Environmental, Social, and Governance (ESG) and Sustainable Development Goals (SDG) can be the main foundation for implementing sustainability programs. Amidst competition with its competitors, Blibli strongly demonstrates its commitment as a business that is sensitive to environmental sustainability by creating the Blibli Tiket Action, one of which is the Langkah Membumi Festival event. Blibli collaborates with many stakeholders and runs the Langkah Membumi Festival event consistently and continues to provide innovations every year. However, many people still lack concern and are unaware of the importance of sustainability. Therefore, this study aims to analyze Langkah Membumi Festival 2024 stakeholder engagement and Blibli Tiket Action's sustainability goals in increasing public awareness regarding the environment and sustainable ecosystems, using the concept of Preparation, Engagement, Perpetuation (PEP). This study uses qualitative methods, through interviews with five informants, literature studies, and document studies of journal articles, company reports, and media reports. The results of this study indicate that Blibli Tiket Action uses a pentahelix approach to attract its stakeholders and chooses a concept plan that suits its stakeholders' lifestyles. In the Preparation phase, thorough planning and systematic stakeholder mapping were carried out. The Engagement phase highlights various participatory activities that successfully enhance involvement, while the Perpetuation phase focuses on efforts to sustain awareness and ensure long-term impact.